Fire Alarm System - Putrie Aurelia Riyono; Aprilian Sasi Kirana Purwa Saputra; Hendi Jadi Ate; Fatur Rahman; Restu Mukti Utomo (Politeknik Negeri Samarinda, 2020)
Fire is an accident that often occurs in the community. For that we need a tool that can provide early warning of a fire. There are many types of fire alarms. We design a fire alarm system using a microcontroller. By using this fire sensor, if a fire is detected, the sensor will send a signal regarding the presence of a fire. Flame sensor will be connected to the microcontroller. In this study using a microcontroller in the form of Wemos D1 and a flame sensor as a fire detection sensor and as an indicator light. The flame sensor itself can detect waves of 760 nm – 1,100 nm. Wemos D1 which functions as a microcontroller will send a signal to turn on the buzzer as an alarm and a dynamo which is used to turn on the pump.